Jaringan Edukasi Negeri dalam Literasi Anak Pelosok menuju Multiliterasi Berbasis Learning Cycle 5 E Siswa MIS Guppi Pattalassang - Fatikha Ulyya; Nur Faizah; Muh. Azriel Putra Rizal; Nurul Azizah Azzahrah; Saenal Ashar; Misdar Amdah; Erman Syarif (LaGeografia, 2024)
The education gap in Indonesia, which is influenced by geographical factors, hinders access to proper education in remote areas. Through the Community Service Programme (PKM-PM) ‘Jendela Pelosok,’ it is expected to contribute to improving reading literacy for students, especially in remote category schools. This study aims to evaluate the effect of the Learning Cycle 5E learning model in improving students' reading and writing literacy at MIS Guppi Pattallassang, Pao Village, Tombolo Pao Sub-district, Gowa Regency. This study used mixed methods with qualitative-descriptive and quantitative-experimental approaches, as well as a pretest-posttest design. The results showed that the application of Learning Cycle 5E learning model was effective in improving students' literacy. The pretest data showed an average score of 42.50 for writing ability and 43.56 for reading ability before the model was applied. After the application of the Learning Cycle 5E learning model, the posttest data showed an increase in literacy scores to 70. The Learning Cycle 5E learning model consists of five stages: engagement, exploration, explanation, elaboration and evaluation.